PENGARUH WORK LIFE BALANCE, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT. WIRAKIMFOOD INDONESIA - Muhammad Agung Satriyo Utomo; Diah Ayu Sanggarwati (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
This study investigates the impact of work-life balance and work motivation on employee performance at PT. Wirakimfood Indonesia, both individually and collectively. It employs quantitative research methods, utilizing a 1-5 Likert scale and multiple linear regression analysis via SPSS 24 software. Data was gathered through a questionnaire distributed through a Google form link. The study's sample consisted of 50 employees from PT. Wirakimfood Indonesia, selected using non-probability purposive sampling. Findings reveal that both work-life balance and work motivation significantly and positively affect employee performance, both individually and together. The coefficient of determination shows that these two variables account for 70.2% of the variation in employee performance, with the remaining 29.8% influenced by other factors not covered in this research.